1992
DOI: 10.1111/j.1600-0773.1992.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Potassium and Calcium in Rat Myocardium Exposed to α‐1‐Adrenoceptor Stimulation

Abstract: Net fluxes of potassium, calcium, sodium and chloride were examined in isolated perfused rat hearts during alpha-1-adrenoceptor stimulation. The ion measurements were performed in the non-recirculating perfusate. Hearts were exposed to alpha-1-adrenoceptor stimulation (phenylephrine 5 x 10(-5) mol/l in the presence of the beta-blocker timolol 10(-6) mol/l). During alpha-1-adrenoceptor stimulation perfusate potassium fell relatively rapidly by about 0.10 mmol/l after approximately 100 sec. followed by a slower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The cells were also capable of responding functionally to receptor stimulation, as they showed enhanced uptake of 86Rb+ after al-adrenoceptor stimulation with phenylephrine. This is in accordance with recent reports of an increased potassium uptake during aladrenoceptor stimulation in perfused beating rat hearts (Hanem et al 1992(Hanem et al & 1993. To our knowledge, this is the first time 86Rb+-uptake has been measured as a functional response to al-adrenoceptor stimulation in enzymatically isolated quiescent cardiomyocytes from adult rats.…”
Section: Discussionsupporting
confidence: 94%
“…The cells were also capable of responding functionally to receptor stimulation, as they showed enhanced uptake of 86Rb+ after al-adrenoceptor stimulation with phenylephrine. This is in accordance with recent reports of an increased potassium uptake during aladrenoceptor stimulation in perfused beating rat hearts (Hanem et al 1992(Hanem et al & 1993. To our knowledge, this is the first time 86Rb+-uptake has been measured as a functional response to al-adrenoceptor stimulation in enzymatically isolated quiescent cardiomyocytes from adult rats.…”
Section: Discussionsupporting
confidence: 94%
“…All effects were prevented by the selective a-1adrenoceptor antagonist prazosin, thus confirming the involvement of this receptor type. An increase in intracellular potassium content based upon indirect measurements has previously been reported in heart (Ellingsen et al 1987;Hanem et al 1992). Direct measurements of intracellular potassium content and concentration in rat hearts after a-1-adrenoceptor stimulation have not to our knowledge been reported previously.…”
Section: Discussionmentioning
confidence: 69%
“…From electrophysiological studies on myocardial preparations, it has been established that outward potassium currents are reduced after a-I-adrenoceptor stimulation (Apkon & Nerbonne 1988;Wang et al 1991;Fedida et al 1993;Terzic et al 1993). Accumulation of potassium in hearts exposed to a-1 -adrenoceptor stimulation has been observed (Ellingsen et al 1987;Hanem et al 1992). In those two studies, however, the potassium accumulation was estimated indirectly by measuring the change in the arteriovenous differences.…”
mentioning
confidence: 99%
“…a,-Adrenoceptor stimulation decreases several outward K+-currents in rat ventricular cardiomyocytes (Fedida et al 1993;Terzic et al 1993). Studies using radioactive isotopes or measuring ionic concentrations, however, demonstrated both increased 86Rbf-influx (Hanem et al 1994a) and increased K+-influx (Ellingsen et al 1987a;Hanem et al 1992) and increased 86Rbf-efflux (Hanem et al 1993), resulting in net increased K+-uptake (Hanem et al 1994b). P-Adrenoceptor stimulation has also been shown to increase the K+-uptake in the heart (Ellingsen et al 1987a), and it was shown that this effect was mediated via stimulation of the P1-adrenoceptors (Ellingsen et al 1987b).…”
mentioning
confidence: 99%